Cálculo do Índice de Mobilidade Urbana Sustentável (IMSCAMP) na Universidade Federal do Pará - Campus Belém - MATOS, Ana Carolina de Almeida (2024)
Over the years, the increasing prioritization of motorized transport modes by society, as the main means of travel, has led to negative consequences for the environment and significant challenges for transportation. This phenomenon boosted the relevance of the discussion on the sustainability of modern cities. Therefore, this study aims to investigate the conditions of sustainable urban mobility on the Belém Campus of the Federal University of Pará, through the application of the Sustainable Mobility Index for University Campus – IMSCamp, developed by Oliveira (2015), focusing on the domain of “infrastructure”. To this end, the characteristics of the campus related to motorized and non-motorized modes of travel, as well as accessibility issues, were analyzed through questionnaires applied to campus users and engineers specializing in transport, in addition to carrying out data collection in the field, adopting the methodology proposed by Oliveira (2015). The index result was 0.462 for the campus, on a scale from 0, considered very bad, to 1, considered very good. Therefore, the result is considered unsatisfactory. However, in a comparative ranking between 04 university campuses that used the same method, although the index result was low, the Belém campus was positioned in 2nd place, among the 04 evaluated. It is noteworthy that the main challenge identified for the Belém Campus was the “Campus access infrastructure” indicator, which presented the lowest performance among those analyzed. The indicator “Quality of roads on Campus” represented the greatest satisfaction among users. These results indicate the need for targeted actions to improve the conditions of sustainable mobility both at the macro level, referring to the city of Belém, and in the surroundings of large Travel Generating Centers, such as the UFPA Belém Campus, making use of isolated results of each indicator in this study to guide intervention strategies for improvements.